THE INFLUENCE OF WORK MOTIVATION AND WORK ON EMPLOYEE PERFORMANCE IN OFFICES TRADE AND INDUSTRY GOWA DISTRICT - Hariyana, Hariyana; Asriati, Asriati; Syarifuddin Sulaiman (International Journal of Economic Research and Financial Accounting, 2024)
This study aimed to describe and test the Influence of Work Motivation and Work Environment on Employee Performance at the Office of Trade and Industry of Gowa Regency. The population and sample in this study were 35 respondents. It is known that the significant value in this study is the Influence of Work Motivation (X1) on Employee Performance (Y) at 0.017 < 0.05, and the calculated value of 2.518 > the table value of 1.694. Meanwhile, the influence of the work environment (X2) on employee performance (Y) is 0.015 < 0.05, with a calculated value of 2.573 > 1.694. The type of data used in this study is quantitative data obtained from questionnaires distributed to respondents. The data sources used in data collection include primary and secondary data. The research instrument used in this study utilized the Likert scale method. Based on the results of this study using statistical calculations through the Statistical Package for the Social Sciences (SPSS) application version 27, the author concludes that work motivation and the work environment have a positive and significant effect on employee performance at the Office of Trade and Industry of Gowa Regency.